(untitled) (Research, Society and Development, 2022)
This work deals with a systematic literature review and aims to analyze and interpret the use of the WhatsApp application in the educational processes of digital literacy. For its execution, an analysis was developed in 10 articles that addressed this theme in order to analyze the use of the WhatsApp application as an educational tool. To search for the bibliography, works published between 2015 and 2021 were used, in English, from two digital repositories – ACM Digital Library and ScienceDirect. However, the analyzed works showed an increase in the use of mobile applications in Elementary School. It was found that teachers consider the use of the WhatsApp application an attractive tool for teaching digital literacy, as it contributes to the reading and writing process of students, both in the school environment and in the extra-school context.